Rancang Bangun Pengontrolan Suhu Pada Sleepingbag Sebagai Tindakan Pencegahan Pada Penderita Hipotermia - Fauzi Awal Ramadhan; Rizal Maulana; Wijaya Kurniawan (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
The advent of climbing in Indonesia can not be denied by the jump in number of climbers every year. Climbing is widely done in September through December where the moon presents its natural beauty to its maximum. But during the month, the Mountains had very cold temperatures due to the extremely high rainfall. Where very high rain rains cause some risks, especially those related to the health of climbers such as colds, injuries from power (heart, and muscle) and hypothermia. This condition often attacks climbers who do not carry complete climbing equipment, are exposed to rain and lack of calorie or other consumption. Based on that background, this study is designed to design Temperature Control on Sleepingbag as a Relief Action on Hypothermia Patients. In this research the writer uses two components namely bracelet and sleeping bag. The bracelet acts as a transformation to get data from the body which is an object then sent to the sleeepingbag that serves to warm the body of hypothermia based on the inputs obtained from the bracelet. Thesis research is intended to design and implement temperature controlling on sleepingbag as a precautionary measure for hypothermia that often occurs in mountainous areas as well as for the development of domestic industry in the field of medical devices. The results of this study indicate that the bracelet system and sleeping bag system work according to the human body condition. The bracelet system will tell the data obtained from the sensor through the LCD display, when the pulse sensor gets the body data less than 60 then the lcd will show that you are detected hypothermia. Then the user will press the button to trim data to sleepingbag to process the data with fuzzy method. Where if the body temperature is less than 35â°C and the sleep sleeping bag is less than 28 then the sleeping bag system will unveil the heating output in the form of full nickel wire according to the rule made in matlab.